Community-Based Adaptation Approaches to Climate Change: Social and Equitable Resilience in East Boston - Lee, Robyn. (Tufts University. Tisch Library., 2023)
Thesis (M.A.)--Tufts University, 2023.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Christine Cousineau.; Keywords: Urban planning, and Climate change.